MANAJEMEN PEMBELAJARAN DALAM MENINGKATKAN PERKEMBANGAN BAHASA ANAK USIA DINI MELALUI MEDIA FLASHCARD 3D - Abu Hasan Agus R; Fathor Rozi; Saputri Fatur Andira (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
The purpose of this study was to determine children's language development through 3-dimensional flashcard media at TK PGRI 1 Banyuglugur, Situbondo Regency. The subject of this observation was group B students, consisting of 20 children consisting of 10 boys and 10 girls. The method used in this research is descriptive qualitative research.The data collection technique is by interview, observation and documentation.In this study, developing aspects of language development due to the low level of children's ability to recognize letters and vocabulary made researchers make 3-dimensional flashcard learning media.3 dimensional flashcard satisfactory result.That way learning using 3-dimensional flashcard media is successful and children's language development increases.